PENGARUH SUKU BUNGA BI, KREDIT PERBANKAN, DAN FOREIGN DIRECT INVESTMENT (FDI) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA - Dimas Prayoga; Josua Sihombing; Puty Andini; Safuridar Safuridar (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of the Bank Indonesia interest rate (BI Rate), banking credit, and Foreign Direct Investment (FDI) on the Indonesia Composite Stock Price Index (IHSG) during the period 2005–2024. The research employs multiple linear regression analysis using the Ordinary Least Squares (OLS) approach with secondary data obtained from the Indonesia Stock Exchange (IDX), Bank Indonesia (BI), and the World Bank. The results indicate that the three independent variables BI Rate, banking credit, and FDI have a significant effect on IHSG, either partially or simultaneously. The BI Rate has a negative and significant influence, while banking credit and FDI have positive and significant effects. The adjusted coefficient of determination (Adjusted R²) of 0.9591 shows that 95.91% of the variation in IHSG can be explained by these variables, while the remaining 4.09% is influenced by other factors outside the model. These findings confirm that maintaining monetary stability, increasing productive credit, and encouraging foreign investment play crucial roles in strengthening Indonesia’s capital market performance. Therefore, policies should focus on maintaining interest rate stability, expanding credit distribution, and creating a conducive investment climate to support a sustainable and resilient capital market.